Impact of the COVID-19 Pandemic on Prenatal Care Utilization Among Italian and Immigrant Pregnant Women: A Multicenter Survey - Luz Maria Vilca; Luz Maria Vilca; Laura Sarno; Davide Passoni; Patrizio Antonazzo; Edda Pellegrini; Maurizio Guida; Elena Cesari; Irene Cetin (Frontiers Media S.A., 2024)
Objectives: To compare the utilization of prenatal services between immigrant and Italian women during the COVID-19 pandemic.Methods: A cross-sectional survey was conducted at 3 maternity care centers in Italy.Results: We included 1,312 women, 1,198 (91.3%) were Italian and 114 (8.7%) were immigrants. A significantly higher proportion of Italians underwent 8 or more prenatal care visits (64.4% vs. 54.4%, p = 0.03) and more immigrants than Italians attended their appointments at hospital settings (45% vs. 18%, p < 0.001). Regarding prenatal course, Italians were more likely than immigrants to attend a non-hospital setting or an online class (49.6% and 30.2% vs. 34.9% and 11.6%, p = 0.008). A higher influenza vaccine uptake among immigrants compared with Italians was observed (39.5% vs. 19.8%, p < 0.001). Among women not receiving certain prenatal services, immigrants were more likely to state COVID-19 pandemic was the main reason for non-compliance.Conclusion: Immigrant pregnant women were more likely to receive prenatal services at a hospital setting than their Italian counterparts. Among women who did not comply with prenatal services, immigrants were more likely to cite the pandemic as their main reason.